The Quantum Statistical Mechanical Theory of Transport Processes - Ali Maghari (Iranian Journal of Chemistry & Chemical Engineering, 1993)
A new derivation of the quantum Boltzmann transport equation for the Fermion system from the quantum time evolution equation for the wigner distribution function is presented. The method exhibits the origin of the time - irreversibility of the Boltzmann equation. In the present work, the spin dependent and indistinguishibility of particles are also considered.